2011
DOI: 10.1007/s00431-011-1547-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice

Abstract: The aim of this review is to give insight on the benefits and risks of vegetarianism, with special emphasis on vegetarian child nutrition. This eating pattern excluding meat and fish is being adopted by a growing number of people. A vegetarian diet has been shown to be associated with lower mortality of ischaemic heart disease and lower prevalence of obesity. Growth in children on a vegetarian diet including dairy has been shown to be similar to omnivorous peers. Although vegetarianism in adolescents is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 47 publications
0
54
0
4
Order By: Relevance
“…The results of several clinical trials, as well as statements of paediatric experts, concluded that a well-balanced vegetarian diet can provide nutritional needs for growing children and adolescents [15,25], but some more restrictive vegetarian diets (such as a vegan diet) might lead to a higher risk of iron, vitamin B12 and calcium deficiency [15,26,27]. Our results suggest that Polish vegetarian children might not follow a well-balanced diet, which should contain sources of energy and nutrients from a variety of foods (eggs, dairy products, grain products, vegetables and fruit).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of several clinical trials, as well as statements of paediatric experts, concluded that a well-balanced vegetarian diet can provide nutritional needs for growing children and adolescents [15,25], but some more restrictive vegetarian diets (such as a vegan diet) might lead to a higher risk of iron, vitamin B12 and calcium deficiency [15,26,27]. Our results suggest that Polish vegetarian children might not follow a well-balanced diet, which should contain sources of energy and nutrients from a variety of foods (eggs, dairy products, grain products, vegetables and fruit).…”
Section: Discussionmentioning
confidence: 99%
“…The negative correlation between iron supply and the age of vegetarian children suggests that younger children, who are fed by their parents, have a more iron-rich diet than adolescents, who have more of a say in what they eat and may develop inappropriate eating behaviors [32]. Therefore, there is a need to educate parents and adolescents specifically on how to enrich their diet (depending on the child's age) with good iron sources allowed in the vegetarian diet (seeds, prunes) and increase iron absorption from the diet by adjusting food preparation techniques, food selection and food combinations [27,33,34]. The importance of such education is additionally confirmed by the fact that other Polish researchers who examined haematological parameters in vegetarian children of similar age (consulted in the advisory service for vegetarians) concluded that these markers have normal values [35].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin B12 is exclusively found in animal products including meat, eggs, fish and milk [11]. Vitamin B12 is a cofactor for two important metabolic reactions: methylation of homocysteine to methionine which is subsequently converted into S-adenosylmethionine and conversion of methylmalonyl CoA to succinyl CoA.…”
Section: Introductionmentioning
confidence: 99%
“…However, most infants with B12 deficiency are born to women with low vitamin B12 levels and have been exclusively breastfed. Vitamin B12 is only found in animal products such as meat, egg, fish and milk [4]. Consequently, the breast milk of mothers who do not consume such products is frequently poor in vitamin B12, and their newborn infants have low vitamin stores.…”
Section: Introductionmentioning
confidence: 99%